Smart Parking System Using IoT with Ultrasonic Sensor - Nik Mohd Farhan Azizi Baharul Azmi; Mohd Badrulhisham Ismail (Journal of Engineering Technology, 2022)
This report describes the Smart Parking System Using IoT with Ultrasonic Sensor project. In this modern world with a lot of vehicles, the demand for a mechanism to determine the availability of parking spaces in local parking garages. The project also seeks to give functionality and adaptability based on future "smart" gadgets and integrate the device into an Internet of Things (IoT) system. At the moment, cars must manually navigate the parking garage to find a parking spot. Drivers can see how many available parking spots are with our proposed method. Using a network of ultrasonic sensors, the final solution is achieved. These sensors send data to a database that may be viewed through a graphical user interface. This research is expected to give the data needed to implement the network in the real world. This system could be done cheaply, and future device growth could be incorporated.